The Use of Islamic Song Media to Increase Students' Interest in Learning the Pillars of Faith Material at SD Negeri 0901 Tanjung Baringin - Samosir, Nurmida; Pohan, Siti Masliner; Siregar, Nelly Kasuma (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to improve the learning interest of grade 1 students of SD Negeri 0901 Tanjung Baringin through the use of Islamic song media on the material of the Pillars of Faith. The problem faced is the low interest of students in learning Islamic Religious Education (PAI), especially on the material of the Pillars of Faith, which has an impact on less than optimal learning outcomes. This study uses the Classroom Action Research (CAR) method with a cycle approach that includes the stages of planning, implementation, observation, and reflection. Islamic song media was chosen as a tool to attract students' attention and create a pleasant learning atmosphere, so that students can more easily understand and remember the material of the Pillars of Faith. In the first cycle, the introduction of Islamic songs in learning received a positive response from students, which can be seen from the increase in their involvement in class activities. The evaluation results showed that most students experienced an increase in understanding and interest in learning. This study shows that the use of Islamic song media can increase students' interest in learning in a more enjoyable and interactive way. Therefore, Islamic song media has proven effective in increasing students' interest and learning outcomes on the material of the Pillars of Faith in grade 1 of SD Negeri 0901 Tanjung Baringin